Spinoglenoid ganglion cyst causing supra-scapular nerve entrapment - Imhoff, A. B. (1997)
A 26-year-old tennis player with no self-observed shoulder trauma had weakness and posterior shoulder pain for more than 10 weeks. Clinical examination showed pain and weakness in the region of the infraspinatus fossa with external rotation, abduction and when moving the elbow backward and forward. Multidirectional instability was found on both sides. Plain radiographs showed a round posterior glenoid rim, a reversed Hill-Sachs lesion and bone erosion in the spinoglenoid notch. Sonography revealed a cystic tumour in the infraspinatus fossa. The patient was operated through a classical dorsal approach. A large ganglion cyst was resected, together with the spinoglenoid ligament. After smoothing of the eroded bone, a shift of the posterior capsule was performed. Conclusion: Ganglia as a cause of splenoglenoid nerve entrapment are very uncommon. In some cases of neuropathy of the supracapsular nerve, the cause can be found by good examination, particularly EMG, CT or MRI scan.